A Review on Remediation Technology and the Remediation Evaluation of Heavy Metal-Contaminated Soils - Lei Xu; Feifei Zhao; Xiangyu Xing; Jianbiao Peng; Jiaming Wang; Mingfei Ji; B. Larry Li (Toxics)
With the rapid development of industry and agriculture, soil contamination has become a significant environmental issue, and the heavy metal contamination of soils is an important part of it. The main methods for the remediation of heavy metal-contaminated soils include physical methods, chemical methods, biological methods, and combined remediation methods have been proposed as research deepens. However, the standards and evaluation methods for the remediation of heavy metal-contaminated soils are still not well-established. This article discusses the sources and contamination status of heavy metals in soils, the advantages and disadvantages of remediation technology for heavy metal-contaminated soils, remediation standards, and post-remediation evaluation methods. It also proposes scientific issues to be addressed in future research and provides an outlook on future development, hoping to assist in subsequent remediation studies of heavy metal-contaminated soils.